Deacons’ Approachability on a Structural and Organisational Level (Nordic Journal of Practical Theology, 2026)
A fundamental precondition for deacons’ caregiving ministry is that both the service and its practitioners are perceived as accessible and approachable. This article explores how deacons’ approachability is shaped by structural and organizational conditions in the Church of Norway. The analysis draws on ecclesial governance documents, perspectives from professional theory, and existing diaconal research, and analytically it distinguishes between structural and organizational levels. The article demonstrates that deacons’ approachability is not only a matter of personal qualities or professional competence, but also of power, representation, organization, and institutional frameworks. It argues that approachability functions as a normative ideal in diaconia, while this ideal is only to a limited extent institutionally supported.
Keywords: Deacons; Approachability; Competence; Church structure; Church organization; Professional values; Power